Ukrainian futurism : a historical and critical study - Ilnytzkyj, Oleh S. (Oleh Stepan) (Harvard series in Ukrainian studies,, 1997)
This volume places - for the first time in an English-language work - Ukrainian Futurism within the context of other major Ukrainian literary movements of the time and examines its relationship to Russian and European progressive literary movements. It also outlines Ukrainian Futurism's development in terms of theory and politics and carefully examines representative samples of prose and poetic output of major Futurists. Textual examples are given both in the original Ukrainian and in English-language translation. Ukrainian Futurism, 1914-1930 will be of great value to all those interested in twentieth-century European literary movements in general and Ukrainian literature and culture specifically.